GeneUp: A Program to Select Short PCR Primer Pairs that Occur in Multiple Members of Sequence Lists. (July 1998) - Pesole, G.; Liuni, S.; Grillo, G.; Belichard, P.; Trenkle, T.; Welsh, J.; McClelland, M.
A computer program is presented that selects a small set of short primer pairs for PCR to sample all the sequences in a user-specified list of mRNAs. Such primer pairs could be used to increase the probability of sampling mRNAs of particular interest in differential display and to generate simplified hybridization probes for DNA chips or arrays. The program uses simulated PCR to find pairs of primers that sample more than one sequence in the list. A small set of such primer pairs is selected that give maximal coverage of the sequences in the list. Primer pairs are excluded that: (i) generate simulated PCR products of the same size from a number of sequences in the list, (ii) can easily form primer dimers, (iii) are outside a specified range of G+C content or (iv) occur in another list of undesirable sequences, such as rRNAs and Alu repeats. Five lists consisting of from 48—285 cDNA sequences were used to test the program. A small number of pairs of primers, 8—10 bases in length, were selected that fit the above criteria and that generate one or more simulated PCR products in all or most of the cDNAs in each list.